Coverage Of Changes In The Cultural And Educational Sphere In The Press Of Perestroika - Shaimkulov Azamat Xolmuratovich (Genius Journals, 2025)
This article examines the role of the press of the perestroika era in the changes in the cultural and educational life of the country, as well as in their coverage. The article highlights the fact that as perestroika has become deeply rooted in the life of society, a wide opportunity has opened up to approach the cultural and spiritual heritage from a new perspective, as well as to the scientific analysis of problems.
Keywords: perestroika; periodical press; historical figures